Clinical case of secondary arterial hypertension in the practice of a pediatric - N. A. Belykh; Y. S. Kucheryavenkova; I. V. Piznyur; A. Yu. Lashkov; N. A. Anikeeva (Медицинский вестник Юга России, 2024)
Arterial hypertension (AH) is one of the risk factors for the development of cardiovascular diseases. The frequency of detection of hypertension among the child population ranges from 1 to 18% of the examined children. In recent decades, there has been a rapid increase in the incidence of this pathology worldwide. At the same time, primary hypertension accounts for 10% of children with hypertension under the age of 10 years, and secondary (symptomatic) — 90%. Literature data indicate that hypertension, which occurred in childhood, persists in adults, thereby increasing the risk of mortality from cardiovascular pathology. Among all cases of hypertension in children, in 5–10% of cases, the cause is renal artery stenosis. The article presents data on the prevalence and etiology of secondary hypertension, as well as own clinical observation of the course of this disease in a 17-year-old teenager. The diﬃculties of diagnosing secondary hypertension in pediatric practice are described.